Experimental investigation of the applicability of a thermoelectric generator to recover waste heat from a combustion chamber. (15th August 2015) - Aranguren, P.; Astrain, D.; Rodríguez, A.; Martínez, A.
Highlights: Applicability of turning waste heat into electricity by thermoelectricity. The thermoelectric prototype produces 21.56 W of net energy covering 0.25 m 2 . Study of different variables under real conditions. Heat pipes outperform the conventional finned dissipators by 43% increase in power. Study on heat losses along the chimney obtains a 2.2% thermoelectric efficiency. Abstract: A thermoelectric generator prototype has been built; it produces 21.56 W of net power, the produced thermoelectric power minus the consumption of the auxiliary equipment, using an area of 0.25 m 2 (approximately 100 W/m 2 ). The prototype is located at the exhaust of a combustion chamber and it is provided with 48 thermoelectric modules and two different kinds of heat exchangers, finned heat sinks and heat pipes. Globally, the 40% of the primary energy used is thrown to the ambient as waste heat; one of the many different applications in which thermoelectricity can be applied is to harvest waste heat to produce electrical power. Besides, the influence on the thermoelectric and on the net power generation of key parameters such as the temperature and mass flow of the exhaust gases, the heat dissipation systems in charge of dispatching the heat into the ambient and the consumption of the auxiliary equipment has been studied. In terms of heat dissipation, the heat pipes outperform the finned dissipators, a 43% more net power is obtained.